Comparative evaluation of remaining dentin thickness, canal centering ability and apical deformity between ProFit S3 and Protaper gold - A nano CT study - S. Swathi; Delphine Priscilla Antony; Pradeep Solete; Ganesh Jeevanandan; Satish Vishwanathaiah; Prabhadevi C. Maganur (Elsevier, 2024)
Purpose: For the root canal treatment to be successful, the root canal system must be cleaned and shaped, and must be gradually widened from the apical to the coronal region in order to preserve dentin thickness. ProFit S3 (Profit Dental, India) patented rotary file with variable taper design preserves dentin. The study employs ultra-high-resolution nano-computed tomography to assess the volumetric changes of two new rotary files in permanent mandibular premolars. Materials and methods: Based on inclusion and exclusion criteria, this in-vitro investigation used extracted premolars. Before the pre-operative scan, samples were made and the working length was determined using a high-precision nano-CT (SkyScan 2214, Bruker, Kontich, Belgium). A single skilled pediatric dentist used ProFit S3 (Profit Dental, India) and Protaper Gold (PTG; Dentsply, Tulsa Dental Specialties, Tulsa, OK, USA) to prepare the canals. Post-op scans were similar to pre-ops. For 3D root canal visualization and analysis, NRecon software was used to rebuild images. Results: Profit S3 has a mean value of 0.65500 and Protaper gold 1.38800, indicating a significant range. Protaper gold followed Profit S3 in canal volume differential. The two rotating file systems differed significantly (p 0.05). ProFit S3 maintained mesiodistal and buccolingual dentin thickness at 4 mm, 8 mm, and 12 mm, followed by Protaper Gold. Conclusions: ProFit S3 exhibited the lowest mean canal volume difference compared to Protaper gold. Unlike Protaper Gold, ProFit S3 offers a variable taper design that preserves root canal anatomy, peri cervical dentin, and dentin thickness.